Визначення фізико-технічних властивостей керамічної цегли та її гідрофобний захист - Семенів, Р. М.; Semeniv, R. (Видавництво Львівської політехніки, 2018)
У статті досліджено фізико-технічні властивості керамічної цегли. Встановлено, що вирішальним факторами в процесах взаємодії керамічної цегли з водою, водними розчинами та водяною парою є склад, порова структура та енергетичний стан її поверхні. Обґрунтовано та визначено компонентний склад та технологічний режим формування захисного покриття на поверхні керамічної цегли. Визначено технологічні властивості вихідних композицій та фізико-механічні показники покриттів на їх основі. Встановлено вплив складу вихідної композиції захисного гідрофобного покриття на водостійкість керамічної цегли. Підтверджено можливість використання розроблених складів захисних покриттів для гідрофобного захисту поверхні керамічної цегли та підвищення довговічності будівель та споруд, які експлуатуються в умовах підвищеної вологості та дії зовнішніх агресивних чинників

The current article is focused at the physical and technical properties of ceramic bricks. It was established that the decisive factors in the process of interaction of ceramic bricks with water, water solutions and water vapor is the composition of pore structure and energy state of its surface. It is substantiated and defined the component composition and technological regime of the protective coating formation on the surface of ceramic bricks. The technological properties of the initial composition and physico-mechanical properties of coatings based on them are established. It is revealed the influence of initial composition compound of the protective hydrophobic coating to water resistance of ceramic bricks. Confirmed the possibility of using the developed composition of protective coatings to hydrophobic surface protection ceramic of bricks and increase the durability of buildings and structures, that are exploited in the high moisture condition and the action of external and aggressive factors. It is widely used the method of surface impregnation by repel compounds, resulting the reduction of porosity and permeability of the material to improve the performance properties and increase the durability of brick masonry. The right choice of hydrophobic composition determines the durability of masonry in different conditions of buildings exploitation.
Research of physical and technical properties of ceramic bricks and its hydrophobic protection
Keywords: керамічна цегла; водопоглинання; захисне покриття; водостійкість; гідрофобність; ceramic brick; water absorption; protective covering; water resistance; hydrophobicity; 691.42